Multilevel Reading as an Epistemological Model of Islam-Science Integration: A Critical Study of Nidhal Guessoum - Mohammad Muslih; Erni Puryati Ningsih; Rahmat Ardi Nur Rifa Da’i; Adi Setiawan (Center of Islamic and Occidental Studies, 2026)
This article aims to examine and analyze Nidhal Guessoum’s concept of multilevel reading as an epistemological model of Islam-science integration. Specifically, it investigates the epistemological foundations, methodological structure, and logical consistency of Guessoum’s approach in reconciling revelation and scientific rationality. Employing qualitative library research, this study uses epistemological, hermeneutical, and philosophy of science approaches to critically evaluate Guessoum’s thought. The findings show that multilevel reading represents an attempt to establish a dialogical relationship between religion and science without reducing one into the other. Guessoum rejects both scientism and literalism by proposing contextual and layered interpretations of religious texts. This approach enables a more flexible interaction between Qur’anic interpretation and contemporary scientific developments. However, the study also finds that the model still faces several methodological challenges, particularly regarding interpretive ambiguity and epistemological consistency. Despite these limitations, Guessoum’s framework contributes significantly to the development of contemporary Islamic epistemology by offering a more contextual, critical, and integrative paradigm of Islam-science relations. Therefore, multilevel reading can be regarded as an important alternative model in contemporary discussions on religion and science.